Challenges and advances in the assessment of the disposition of antibody‐drug conjugates. (8th June 2015) - Kamath, Amrita V.; Iyer, Suhasini
Abstract: Antibody‐drug conjugates (ADCs) are a rapidly growing therapeutic platform for the treatment of cancer. ADCs consist of a cytotoxic small molecule drug linked to an antibody to provide targeted delivery of the cytotoxic agent to the tumor. Understanding the pharmacokinetics (PK) and pharmacodynamics (PD) of ADCs is crucial in their design to optimize dose and regimen, to maximize efficacy and to minimize toxicity in patients. Significant progress has been made in recent years in this area, however, many fundamental questions still remain. This review discusses factors to consider while assessing the disposition of ADCs, and the unique challenges associated with these therapeutics. Current tools that are available and strategies to enable appropriate assessment are also discussed. © 2015 Genentech Inc. Biopharmaceutics & Drug Disposition Published by John Wiley & Sons Ltd.